PENGEMBANGAN APLIKASI ABSENSI SISWA MA – ALMUKLISIN BERBASIS WEB - Ahmed Hendra Widjoyo; Annisa Azahra Firdaus; Exi Purnamasari (CV. Multi Kreasi Media, 2024)
Education is an effort to develop human capacity. The means for developing human potential are found in the school environment. School is a place where you are responsible for learning and developing your own values, attitudes and character competencies that are shaped by the education system, curriculum and local environment. Technological developments in recent years have made it easier for people to carry out various activities such as teaching, lectures and office activities. This is considered very useful for someone to get fast, concise and accurate information. Therefore, with current technological developments, educational activities must also be supported. One of the activities is the process of making student attendance which requires time to fill in the absence. The purpose of this survey is to simplify the process by conducting a survey that makes it easier for teachers to take attendance.